AKI in Hospitalized Children: Poorly Documented (and Underrecognized) - Jones, Katherine; Neu, Alicia; Fadrowski, Jeffrey (Frontiers in Pediatrics, 2022)
Background: Acute kidney injury (AKI) is common in hospitalized children. We hypothesized that hospital-acquired AKI would be underrecognized and under-reported, with potential implications for prevention of future AKI and CKD risk stratification. Methods: Five hundred thirty-two cases of AKI occurring over a 1 year period in a tertiary children's hospital in the United States were studied. AKI documentation was defined as any mention of AKI in the admission history and physical note, progress notes, or discharge summary. Nephrology follow-up was defined as a completed outpatient clinic visit within 1 year of discharge. Logistic regression was used to assess factors associated with documentation, consultation, and follow-up. Results: AKI developed during 584/7,640 (7.6%) of hospitalizations: 532 cases met inclusion criteria. Documentation was present in 34% (185/532) of AKI cases and 90 (16.9%) had an inpatient nephrology consult. Among 501 survivors, 89 (17.8%) had AKI in their hospital discharge summary and 54 had outpatient nephrology follow up. Stage 3 AKI, peak creatinine >1 mg/dL and longer length of stay were associated with documentation. Stage 3 AKI and higher baseline creatinine were associated with inpatient nephrology consultation. Inpatient nephrology consultation was positively associated with outpatient nephrology follow up, but documentation in the discharge summary was not. Conclusion: Most cases of AKI were not documented and the proportion of children seen by a nephrologist was low, even among those with more severe injury. Increased severity of AKI was associated with documentation and inpatient consultation. Poor rates of documentation has implications for AKI recognition and appropriate management and follow up.